Determination of Different Parameters to High Strength Steel Clinch Joints by FEA - Jónás, Szabolcs; Tisza, Miklós (International Journal of Engineering and Management Sciences, 2019)
In this article the clinched joints were analyzed by finite element method (FEA). The base materials were advanced high strength steels (DP 600, DP 800 and DP 1000). The model validation procedure was done by the DP 600 type of steel sheets; the other two types of steel were only simulated. The goal was to determine the geometrical properties of the joints with different strength steels. The FEA model was the same in every mechanical point of view therefore the results are comparable. The main geometrical parameters of the clinch joints are the neck thickness (tN), the undercut (C), the bottom thickness (tB) and the height of the protrusion (h); these values were compared.